Creative wooden boxes from the scroll saw : 28 useful & surprisingly easy-to-make projects - Rothman, Carole (Fox Chapel Pub., 2012)
"Carole Rothman, author of the best-selling Wooden Bowls from the Scroll Saw, returns to offer her creative spin on box projects. She's surveyed the most popular boxes in woodworking and shows you how to make bandsaw-style boxes, jewelry boxes, and lidded boxes on the scroll saw. Inside, you'll find 29 beautiful and creative designs for boxes you'll love to make and love to use. Rothman also walks you through the creation of her scroll-sawn bow technique, which she adapted from cake decorating."--